Action Research with Teachers: Children’s Participation and Educators’ Professional Development - Gawlicz, Katarzyna (INSTED: Interdisciplinary Studies in Education & Society, 2022)
This article explores the potential of a networked learning community for supporting teachers’ professional development and transforming children’s life in an educational institution. It draws on a small-scale action research project carried out by a team of Polish early childhood educators and academics who collaborated to create conditions for strengthening children’s participation in preschool. The mode of work combined the teachers’ individual investigation and actions in their settings with monthly meetings of the whole team serving as a space for the participants to support, inspire and challenge each other. Besides the implementation of concrete solutions by the teacher-researchers that enhanced their students participation, the project contributed to the emergence of the teachers’ habit of critically observing, documenting, and reflecting on their practice, increased their confidence as autonomous professionals and change agents, and augmented their view of children as competent decision makers. It is argued that it is the combination of continuous individual critical reflection and regular collaboration that is instrumental in triggering and sustaining such changes.